Preclinical Differences of Intravascular AAV9 Delivery to Neurons and Glia: A Comparative Study of Adult Mice and Nonhuman Primates - Gray, Steven J (Nature Publishing Group, 2011)
Other labs have previously reported the ability of adeno-associated virus serotype 9 (AAV9) to cross the blood-brain barrier (BBB). In this report, we carefully characterized variables that might affect AAV9's efficiency for central nervous system (CNS) transduction in adult mice, including dose, vehicle composition, mannitol coadministration, and use of single-stranded versus self-complementary AAV. We report that AAV9 is able to transduce approximately twice as many neurons as astrocytes across the entire extent of the adult rodent CNS at doses of 1.25 × 10(12), 1 × 10(13), and 8 × 10(13) vg/kg. Vehicle composition or mannitol coadministration had only modest effects on CNS transduction, suggesting AAV9 crosses the BBB by an active transport mechanism. Self-complementary vectors were greater than tenfold more efficient than single-stranded vectors. When this approach was applied to juvenile nonhuman primates (NHPs) at the middle dose (9–9.5 × 10(12) vg/kg) tested in mice, a reduction in peripheral organ and brain transduction was observed compared to mice, along with a clear shift toward mostly glial transduction. Moreover, the presence of low levels of pre-existing neutralizing antibodies (NAbs) mostly occluded CNS and peripheral transduction using this delivery approach. Our results indicate that high peripheral tropism, limited neuronal transduction in NHPs, and pre-existing NAbs represent significant barriers to human translation of intravascular AAV9 delivery.